2000
DOI: 10.1177/002215540004801005
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Within the Nucleus and Neighboring Cytosol Is a Key Feature of Prothymosin-α

Abstract: S U M M A R YProthymosin ␣ is a small, unfolded, negatively charged, poorly antigenic mammalian protein with a potent nuclear localization signal. Although it is apparently essential for growth, its precise function is unknown. We examined the location and behavior of the protein bearing different epitope tags using in situ immunolocalization in COS-1 and NIH3T3 cells. Tagged prothymosin ␣ appeared to be punctate and widely dispersed throughout the nucleus, with the exception of the nucleolus. A tiny cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 63 publications
3
25
0
2
Order By: Relevance
“…On the other hand, monoclonal antibodies are usually characterized by rather low affinity for the corresponding antigen, and consequently, they are also difficult to apply to the development of sensitive competitive immunoassays. This is probably true for the few monoclonals for ProTa reported until now in the literature (Staehli et al 1983;Sukhacheva et al 2002); as a consequence, few immunoassays have been reported for a thymosins and even fewer have been applied to the analysis of biological samples (Panneerselvam et al 1987;Tsitsiloni et al 1994;Costopoulou et al 1998;Mitani et al 2000), whereas their quantitative experimental results seem to vary and therefore have been approached with caution by some researchers (Enkemann et al 2000b). However, provided that their specificity is appropriate, carefully selected antibodies for ProTa may be of great value for certain clinical applications and especially for the immunostaining of tissue samples, in which they can be used in excess.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, monoclonal antibodies are usually characterized by rather low affinity for the corresponding antigen, and consequently, they are also difficult to apply to the development of sensitive competitive immunoassays. This is probably true for the few monoclonals for ProTa reported until now in the literature (Staehli et al 1983;Sukhacheva et al 2002); as a consequence, few immunoassays have been reported for a thymosins and even fewer have been applied to the analysis of biological samples (Panneerselvam et al 1987;Tsitsiloni et al 1994;Costopoulou et al 1998;Mitani et al 2000), whereas their quantitative experimental results seem to vary and therefore have been approached with caution by some researchers (Enkemann et al 2000b). However, provided that their specificity is appropriate, carefully selected antibodies for ProTa may be of great value for certain clinical applications and especially for the immunostaining of tissue samples, in which they can be used in excess.…”
Section: Discussionmentioning
confidence: 99%
“…We strongly believe that the ProTa molecule does behave in a tricky way in the Western blot (Freire et al 2002;Lal et al 2005), and the slightest changes in the experimental conditions may greatly affect its immobilization onto the membrane, which is probably the main reason for the often reported poor Western blotting results. However, under Enkemann et al (2000b), who used COS-1 and NIH3T3 cells transfected with genes of epitope-tagged ProTa proteins in combination with antibodies against the epitope tags. The intensity of the fluorescent signal was stronger in the cancer cells than in normal ones.…”
Section: Discussionmentioning
confidence: 99%
“…The use of cell lines with different genetic alterations are likely to be important, and cell lines with an impaired p53 pathway may predominantly proliferate in response to PTMA. It is furthermore very likely that protein tags significantly alter results for PTMA, such as subcellular localization and biological functions (52,53). We have tested NH 2 -terminally tagged PTMA (FLAG, Myc, and glutathione S-transferase tags) in p53 reporter gene assays and found that none were able to stimulate p53 activity, despite expression levels similar to native PTMA.…”
Section: Discussionmentioning
confidence: 99%
“…For these studies we used immunofluorescence staining to determine if the same cells that express PTa are also proliferating. PTa has been proposed to move between nuclear and cytoplasmic compartments (Enkemann et al, 2000). However the relative importance of nuclear and cytoplasmic localization on its proliferative effects has not been examined.…”
Section: Determination Of the Relevance Of Era Regulation Of Pta Tranmentioning
confidence: 99%